Wilayah Jihad di Dar Al-Islam - Abdullah, Mustaffa (Jurnal Usuluddin, 1999)
Striving in the way of God to spread Islam should be practised based on Muslim’s ability. Therefore this article aims to discuss the implementation of jihad by the prophet Muhammad s.a.w. and his followers at Dar al-Islam after hegira on 622 A.D from Mecca to Medina.